Piezoceramic-polymer composites for detector applications - Preuksa Auisui (2018)
Ferroelectric powders of PbTiO3were fabricated and sintered at low-temperatures. The ceramic pores were filled with an epoxy using a vacuum impregnation technique. SEM analysis showed a composite with 3-3 connectivity. The piezoelectric coefficient of the composite was evaluated as (6.0 ± 1.0) × 10-12m/V by an interferometric technique. The pyroelectric coefficient was 23 μC/m2°C. The pyroelectric detector properties and figures-of-merit of the composite are reported.